Fear emotion reduces reported mitigation behavior in adolescents subject to climate change education - Wang, Xueqi; Chen, Jin (Climatic change, 2022)
Emotion has been recognized as a significant factor affecting climate engagement behavior. However, empirical experiments testing emotions influencing behavioral changes, climate change education (CCE) in particular, are rare. In this study, we conducted a 2-week CCE program with the support of video clips to induce emotions such as fear and/or hope through the manipulated treatments and were then compared between emotion plus lecture group and lecture-only group for adolescents to explore how emotions affect self-reported mitigation behavior toward climate change. The study involved 1730 students from nine middle schools in three coastal cities (Xiamen, Shenzhen, and Ningbo) in China. The results demonstrated that emotional video clips were the successful stimulus for target emotions. There was a significant improvement in both knowledge-gaining and self-reported mitigation behavior in the lecture-only group, and climate change concern and involvement mediated the effect on mitigation behavior. Compared to the lecture-only group, the hope treatment group showed decreased knowledge gain but no significant effect on self-reported mitigation behavior. In contrast, emotion significantly reduced students’ self-reported mitigation behavior in the fear treatment group, which was mostly pinpointed to the behavioral change of emission reduction activities. Thus, the study highlighted the importance of knowledge with appropriate emotions in adolescents to safeguard educational outcomes.